Essentials of language testing for Malaysian teachers - Abd. Samad, Arshad (Universiti Putra Malaysia Press, 2010)
This book first discusses traditional concepts and ideas related to language testing and evaluation. This is followed by an exploration into more recent notions about testing, emphasizing the qualitative and social rather than psychometric aspects of tests. Each chapter presents a brief discussion of important concepts, terminology and issues related to these two perspectives. This book is intended as a bridge between the more traditional concepts of testing and measurement in teaching English as a second language to one that is more contemporary and compatible with modern views of language learning and education. It hopes to address important and relevant issues that can help the reader better understand the demands and challenges of testing and evaluation in TESL especially in Malaysia. While the book is intended for the undergraduate testing course in the TESL programme at Universiti Putra Malaysia, it is also relevant to the needs of language teachers especially in Malaysia schools.